The Mechanisms of GovernanceThe Mechanisms of Governance, by WilliamsonOliver E. New York: Oxford University Press, 1996. - Duhaime, Irene; Mahoney, Joseph T. (Academy of Management Review, 1997)
The article reviews the book ?The Mechanisms of Governance,? by Oliver E. Williamson.